IMPLEMENTATION OF E-GOVERNMENT THROUGH THE VILLAGE FINANCIAL SYSTEM APPLICATION (SISKEUDES) IN LARANGAN VILLAGE, CANDI DISTRICT, SIDOARJO REGENCY - Rohmah, Nabilah Maulidiyah; Rodiyah , Isnaini (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the implementation of e-Government through the Village Financial System (SISKEUDES) application in Larangan Village, Candi District, Sidoarjo Regency, with a focus on the effectiveness of the application's use in village financial management. Method: The method used is a descriptive qualitative approach with data collection through in-depth interviews with village officials, direct observation of SISKEUDES operational processes, and documentation studies of village financial reports. Data analysis was carried out using data reduction, data presentation, and conclusion verification techniques according to the stages of Miles & Huberman. Results:  The results show that SISKEUDES has increased transparency, accountability, and efficiency of village financial management by accelerating the process of recording transactions, financial reporting, and facilitating the realization of the Village Budget (APBDes). However, there are challenges in the form of the need to increase human resource capacity and technological infrastructure that support application optimization. Novelty: The novelty of this study lies in the detailed operationalization of the SISKEUDES application at the village level and the analysis of its impact on more modern and participatory financial governance. These findings provide an important contribution to the implementation of e-Government development policies in other villages in Indonesia, as well as serving as a practical reference for village officials in improving the quality of technology-based financial administration management.